The Urgency of Financial Literacy, Financial Attitude, and Lifestyle on Personal Financial Management of Kartu Indonesia Pintar Scholarship Recipients in the Era of Increasing Digital Fraud - Rosmida, Rosmida; Nurhazana, Nurhazana (Politeknik Negeri Bengkalis, 2024)
Kartu Indonesia Pintar Kuliah (Indonesia Smart Card for College), is one of the government programs in theeducation sector. The purpose of KIP is to provide wider educational opportunities for prospective students fromunderprivileged families who have academic achievements across Indonesia. To achieve the nation's goals andaspirations, it is expected that KIP recipients can complete their studies on time and acquire competencies to improvetheir family's economic condition in the future. Therefore, KIP recipients must wisely manage their personal finances,especially in this era where digital crimes are rampant. Students should understand financial literacy, possess goodfinancial attitudes, and maintain a simple lifestyle. The purpose of this research is to determine the effect of financialliteracy, financial attitudes, and lifestyle on the personal financial management of KIP recipients. The respondents in thisstudy are 100 KIP students from the Public Financial Accounting study program in semesters 3, 5, and 7. The data wereanalyzed using multiple linear regression with the statistical SPSS 25. The results of the t-test and F-test show thatfinancial literacy and financial attitudes have a significant influence on the personal financial management of KIPrecipients, while lifestyle has no significant influence on personal financial management. Simultaneously, financialliteracy, financial attitudes, and lifestyle have a significant effect on the personal financial management of KIP recipients.The coefficient of determination test shows that financial literacy, financial attitudes, and lifestyle variables explain43.7% of the personal financial management variable, while the remaining 56.3% is explained by other variables.